THE ROLE OF DIGITAL DEVICES AND AI-BASED TOOL IN ENHANCING SELF-DIRECTED LEARNING AMONG EFL UNDERGRADUATE STUDENTS OF FERGANA STATE UNIVERSITY - Ominakhon Kodirova (International Journal of Literature and Language Studies, 2026)
This study examines how technology supports self-directed learning (SDL) among undergraduate students at Fergana State University. Using a mixed-methods design, data were gathered from 124 students through a structured questionnaire combining Likert-scale, multiple-choice, and open-ended items. Results show that most students use digital tools daily, especially smartphones and AI-based applications. Technology was found to meaningfully support SDL by improving access to materials, strengthening comprehension through multimedia, and fostering autonomy and motivation. However, persistent barriers remain, including digital distractions, limited self-discipline, unequal internet access, and ethical concerns around AI use and academic integrity. Qualitative responses confirmed that technology is widely viewed as transformative, though its impact depends on students' digital literacy and self-regulation. The study recommends that universities strengthen digital infrastructure, expand faculty training, promote digital literacy programs, and establish clear ethical guidelines for technology use. These findings contribute to the literature on technology-enhanced learning and offer practical guidance for institutions seeking to cultivate independent, motivated learners.